The Effect of Using Macromedia Flash Learning Media on Students’ Higher-Order Cognitive Learning Outcomes in Physics - Putri Zuhra; Fatni Mufit; Lufri (Jurnal Pendidikan Fisika, 2026)
Higher-order cognitive ability is an important competence that needs to be developed in physics learning. However, physics instruction is still often abstract and teacher-centered, which limits its effectiveness in fostering students’ thinking abilities. This study aims to examine the effect of Macromedia Flash learning media on students’ higher-order cognitive ability in physics. A quasi-experimental method with a pretest–posttest control group design was employed. The study involved tenth-grade students divided into experimental and control groups. The research instrument was an essay-based test designed to measure students’ higher-order cognitive ability in physics, predominantly covering the cognitive domains of analyzing (C4), evaluating (C5), and creating (C6). The data were analyzed using an independent samples t-test. The results indicate a significant difference in higher-order cognitive ability between students who learned using Macromedia Flash–based media and those who learned through conventional methods (p < 0.05). Therefore, Macromedia Flash learning media have a positive effect on improving students’ higher-order cognitive learning outcomes in physics. The results suggest that the implementation of Macromedia Flash instructional media has the potential to effectively enhance students' higher-order thinking skills in physics education.